EFFICACY OF BORIC ACID SPRAY FOR CONTROL OF BLACK SCURF IN UNWASHED AND WASHED POTATO TUBERS - Arora, R. K. (Potato Journal, 2013)
Efficacy of 3 per cent boric acid spray treatment was evaluated on both washed and unwashed seed tubers for control of black scurf of potato, a major tuber disease prevalent through out the country. The spray treatment was carried out using a manual sprayer, which do not recycle the solution, and a seed tuber treatment devise which continuously recycle the same solution. The results revealed that the manual sprayer was efficient for both washed and unwashed seed tubers where as only washed and dried tubers could effectively be treated through the seed treatment device.